Surface Plasmon Resonance (SPR) Sensor Based on Optimal Pre- and Post-Selection - Hailin Wang; Wenkang Li; Jianlin Huang; Rui Su; Ruilin Wang; Lan Luo; Yuxia Zhang; Zhiyou Zhang; Quanxi Xue (IEEE Photonics Journal, 2019)
A surface plasmon resonance (SPR) refractive index sensing technique based on the optimal pre-and post-selection (PPS) is put forward. The intensity contrast ratio (ICR) is introduced to estimate the precision of this sensing technique. Compared with the traditional sensing techniques, our method shows that the ICR can be improved by about two orders of magnitude with optimal pre-and post-selected states. It is also proved that our sensing technique has a large tolerance for the metal film thickness and the incident angle. Remarkably, the method greatly reduces the cost of experiments, which is significant for promoting the widespread applications of SPR sensors.